Teacher Professionalization: Is There a Possible Path of Convergence for Experts and Novices? - Mauricio Alejandro Núñez Rojas; Ana Arévalo Vera; Beatrice Ávalos Davidson (Universidad Autónoma de Baja California, 2012)
Paths for the professionalization of teachers have traditionally been conceived of as successive processes that are disjointed from teacher training (initial and ongoing). This leads to the perpetuation of the dichotomy between theory and practice. Closely linked to this last is the lack of communication and even mistrust between the actors involved in different stages of training: academics and in-service teachers. This article explores the idea of professionalization as a process in which the diverse training pathways can converge through permanent situated reflective actions involving the participation of in-service and pre-service teachers, leading to the theorization of practice and the development of increasing levels of professional consciousness for both parties. The experience of communities of practice is regarded as a framework for introducing writing practice, which is seen as a mechanism of empowerment for such professional development.